The Effect of Engineering Design Based Science Teaching on Decision Making, Scientific Creativity and Design Skills of Classroom Teacher Candidates - Elcin Ayaz; Rabia Sarikaya (Journal of Education in Science, Environment and Health)
This study aims to examine the effects of engineering design-based science teaching (EDBST) on classroom teacher candidates’ decision-making skills, scientific creativity and engineering design-based process skills. The random design of the quantitative approach with a pretest-posttest control group was used in the study. The study group consists of 60 teacher candidates convenient sampling method and studying at the Faculty of Education Department of Classroom Education of a state university in Ankara in the 2017-2018 academic year. The implementations of the study continued in the Science and Technology Laboratory Applications-II course for 14 weeks in accordance with the content integration of STEM. Study data were calculated through dependent and independent groups t-test, one-way repeated measures ANOVA and multivariate variance analysis (MANOVA). When the results of the study were examined, it was seen that the skills of the classroom teacher candidates, where the courses were taught with engineering design-based science teaching, developed positively.